Caveolin-1-Knockout Mouse as a Model of Inflammatory Diseases - Elena Codrici; Lucian Albulescu; Ionela Daniela Popescu; Simona Mihai; Ana-Maria Enciu; Radu Albulescu; Cristiana Tanase; Mihail E. Hinescu (Journal of Immunology Research)
Caveolin-1 (CAV1) is the scaffold protein of caveolae, which are minute invaginations of the cell membrane that are involved in endocytosis, cell signaling, and endothelial-mediated inflammation. CAV1 has also been reported to have a dual role as either a tumor suppressor or tumor promoter, depending on the type of cancer. Inflammation is an important player in tumor progression, but the role of caveolin-1 in generating an inflammatory milieu remains poorly characterized. We used a caveolin-1-knockout (CAV1−/−) mouse model to assess the inflammatory status via the quantification of the pro- and anti-inflammatory cytokine levels, as well as the ability of circulating lymphocytes to respond to nonspecific stimuli by producing cytokines. Here, we report that the CAV1−/− mice were characterized by a low-grade systemic proinflammatory status, with a moderate increase in the IL-6, TNF-α, and IL-12p70 levels. CAV1−/− circulating lymphocytes were more prone to cytokine production upon nonspecific stimulation than the wild-type lymphocytes. These results show that CAV1 involvement in cell homeostasis is more complex than previously revealed, as it plays a role in the inflammatory process. These findings indicate that the CAV1−/− mouse model could prove to be a useful tool for inflammation-related studies.